Thriving in adversity Understanding how maize seeds respond to the challenge of combined cold and high humidity stress - Meng, Xiangzeng (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.